Zakat Literacy Improvement in Indonesia: Analysing the Role and Strategy of Center for Strategic Study of the National Amil Zakat Agency (PUSKAS BAZNAS) - Fatmawati, Fatmawati; Hakim, Rahmad; Hakim , Arif Luqman (Iqtishodia: Jurnal Ekonomi Syariah, 2024)
This study aims to describe Puskas BAZNAS' Strategy in Improving Zakat Literacy in Society. The type of research used is qualitative with a case study approach. The data used are primary and secondary data. Primary data collection was obtained from interviews and documentation. While secondary data is in the form of magazines, journals and literature related to Zakat Literacy. This study uses the data validation technique of the triangulation model. The results of the study show that Puskas BAZNAS strategy is quite good and quite effective in increasing community zakat literacy. Evidenced by the significant increase in zakat literacy in society, namely basic understanding increased by 6.8 points, advanced understanding increased by 11.6 points and the average ILZ in 2022 was 8.48 points higher than in 2020 and is also in line with increased literacy community zakat, receipt of zakat funds has also increased from 2019-2022.